Desain Rancang Bangun Inovasi Teknologi Rocket Stove Hemat Energi Dan Turbin Ventilator Sebagai Upaya Optimalisasi Peningkatan Kapasitas Produksi Keripik Ikan Kunir - Yanuar, Setiyo Ferdi; Ana Mufarida , Nely; Darma Setiawan, Orisanto (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
UD. Farah is a well-known trading business in Situbondo that specializes in producing highly sought-after fresh seafood chips called "Ikan Kunir". However, the production capacity is still low due to the use of traditional equipment in the kitchen. To address this, the development of technology using a Rocket Stove is necessary. The Rocket Stove design allows for high-temperature wood combustion, resulting in complete combustion, increased heat energy, and smoke-free operation. It is also more fuel-efficient compared to open fire, saving up to 50% fuel. Furthermore, the current kitchen conditions lack attention to health and safety aspects, leading to smoke-filled, messy, dirty, and dark environments. To improve air circulation and increase production efficiency, a Turbine Ventilator will be installed in the combustion area. This applied research focuses on designing and innovating energy-efficient Rocket Stove technology and utilizing a Turbine Ventilator to enhance the production efficiency of Ikan Kunir chips in terms of time, cost, and energy. The breakthrough aims to improve user health by achieving complete combustion and reducing smoke emissions. The goal of this activity is to address the business partner's challenges, particularly in increasing product capacity and improving occupational health and safety management.